Managing the risks of public infrastructure financing: Toward sustainability - Quanhou Zhao; Wei Liu; Xiaoyang Long; Jiaxi Sun; Xu Chen; Qiongqi Xiao (Asian Development Bank Institute (ADBI), 2020)
Infrastructure construction is one of the basic driving forces of social and economic development. Since 1978, the construction of infrastructure in the People's Republic of China (PRC) has experienced rapid development, which has given a strong impetus to the PRC's modernization. But behind the rapid growth of infrastructure there are risks of a massive and rapid buildup of infrastructure financing. How to manage the risks of infrastructure financing has always been the focus of attention of the Chinese government, as well as economic and academic circles. This paper comprehensively reviews the historical development of the PRC's infrastructure financing and concludes that: (1) the financing of the PRC's public infrastructure construction produces different financing models that are appropriate for various phases facing different real environments and major problems existing in the PRC; (2) with the transformation of the infrastructure financing model, the ways and measures of infrastructure financing risk management are also changing accordingly, and standardization, transparency, and systematization are the main trends in public infrastructure financing and risk management in the PRC; (3) promoting fine management of an infrastructure construction project to ensure the financial sustainability of such a project and then to safeguard the national macrofinancial sustainability is a significant task for the PRC in strengthening the risk management of infrastructure financing.
Keywords: H54; H63; H74; 330; infrastructure finance; risk management; government debt; fiscal sustainability